Right iliac vein thrombosis mimicking acute appendicitis in pregnancy: a case report. (December 2017) - Aroke, Desmond; Kadia, Benjamin; Dimala, Christian; Bechem, Ndemazie; Ngek, Larry; Choukem, Simeon
Abstract Background Right iliac vein thrombosis is uncommon in pregnancy. Nonetheless, when it does occur, its presentation could be very unspecific with important diagnostic challenges and this could have negative therapeutic consequences especially in a resource limited setting. Case presentation The historical, clinical and laboratory data of a 30 year old G2P1001 woman of African ethnicity at 11 weeks of gestation pointed towards a right iliac vein thrombosis missed for an acute appendicitis with subsequent appendectomy and failure to cure. Following the diagnosis of right iliac vein thrombosis post-appendectomy, the patient was started on low molecular weight heparin and the clinical progress thereafter was favourable. Conclusion Pelvic vein thrombosis should be considered a differential diagnosis of intractable lower abdominal pain in early pregnancy. A high index of suspicion could lead to early diagnosis, prompt management and a favourable prognosis even in a low-income setting.